Statistics-Based Optimization of Cellulase and Xylanase Production by the Endophytic Fungus Talaromyces Funiculosus using Agricultural Waste Materials - Syrchin, S.O.; Yurieva, O.M.; Pavlychenko, A.K.; Kurchenko, I.M.; Сирчин, С.О.; Юр’єва, О.М.; Павличенко, А.К.; Курченко, І.М. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
Lignocellulosic biomass can be utilized as a low-cost, renewable, and sustainable feedstock for obtaining non-fossil energy sources with low CO2 emission. One of the most promising technologies for producing 2G biofuels is the saccharification of agricultural waste materials with the help of cellulolytic enzymes, followed by yeast fermentation of sugars into cellulosic ethanol. Cellulases are multi-component enzymes involved in the degradation of cellulose, which can synergistically degrade cellulose and includes three major categories: endoglucanase (EC 3.2.1.4), exoglucanase or cellobiohydrolase (EC 3.2.1.91), and β-glucosidase (EC 3.2.1.21). The core enzyme used for the degradation of the xylan skeleton of hemicellulose is endo-β-1,4-xylanase (EC 3.2.1.8). The high cost of enzymes synthesized by fungi is a bottleneck for the production of cellulosic ethanol. Optimization of the nutrient medium composition is an important factor in increasing the production of enzymes and the efficiency of lignocellulosic biomass hydrolysis. The aim of the current study was to optimize the production of cellulolytic and xylanolytic enzymes through cultivation of filamentous fungus Talaromyces funiculosus on low-cost nutrient media with non-pretreated agricultural waste materials. Methods. Filamentous fungus Talaromyces funiculosus was grown on potato-dextrose agar for 10—14 days at 26±2 °С. To obtain the culture filtrate, the fungus was cultivated under submerged conditions in an Erlenmeyer flask for 4 days. The nutrient medium composition was varied according to the factor experiment design. A two-step optimization of the nutrient medium composition was used. A screening experiment with the Plackett-Burman fractional factorial design and response surface methodology with the Box-Behnken design were used to optimize cellulase production. The enzymatic activity was determined by measuring the reduced sugar production after the enzymes hydrolysis with specific substrates: exoglucanase with filter paper, endoglucanase with carboxymethylcellulose, and xylanase with beech wood xylan, using the colorimetric DNS method with glucose or xylose as a standard. The activity of β-glucosidase was determined by the hydrolysis reaction of p-nitrophenyl-β-D-glucopyranoside, which results in the formation of p-nitrophenol, quantified at 410 nm. Results. As a result of experiments with using agricultural waste, including wheat straw, corn stalk, and corn cob as carbon sources of the culture medium, it was shown that T. funiculosus is able to grow and produce cellulase and xylanase on all non-pretreated substrates studied. The two-step sequential optimization of the nutrient medium composition for T. funiculosus cultivation according to the Plackett-Berman and Box-Behnken designs made it possible to increase the activity of cellulolytic and xylanolytic enzymes by 2.4—2.6 times. The optimized cultivation medium does not contain such expensive components as Avicel, peptone, and yeast extract and has the following composition, g/L: corn stalks — 50.0; urea — 0.86; NaNO3 — 1.0; KH2PO4 — 6.0; KCl — 0.25; MgSO4 — 0.25; FeSO4 — 0.01. Conclusions. The studied strain of T. funiculosus produces a lignocellulosic enzyme complex with a high level of β-glucosidase activity when cultivated on an optimized nutrient medium with untreated agricultural waste and is promising for the conversion of lignocellulosic biomass into fermentable sugars.